SOCIETY AND GOVERNMENT POLICY IN THE ERA OF UMAR IBN KHATTAB AND ITS CONTEXTUALISATION IN INDONESIA FROM THE PERSPECTIVE OF ISLAMIC GOVERNANCE AND MAX WABER'S CHARISMATIC THEORY OF LEADERSHIP - Wahab, Mas Adah; Basar Dikuraisyin (Universitas Negeri Semarang, 2024)
Umar Ibn al-Khattab was the second caliph in Islamic history after succeeding the caliph Abu Bakar al-Siddiq. He was one of the Prophet's companions who had strong morals, was energetic, fair, and wise, had a firm and complex character, and had managerial and administrative skills. Umar as caliph, only ruled for approximately ten years, but in that short period of time, many successes and advances were experienced by the Islamic community, especially in the economic field. So it is common in the history of the Islamic world that Umar's reign was a golden age in Islamic history. The success of Umar's leadership, especially in reforming and developing the economic system of the community and prospering their lives, was due to his scientific ability, ijtihad, and an established managerial system in managing the country's foreign exchange. Proper utilization and distribution, as well as strict supervision and discipline. This can be understood from various political, social and educational economic legal policies. The purpose of the research is to find the concept of auditor independence from the perspective of Umar bin Khattab. This research is qualitative research, using the biographical type tarikh method with the figure Umar bin Khattab. Through tarikh, the author wishes to understand his life. The policies he took were based on the principles of Islamic governance even though they were different from the previous era.